Comparative analysis of current payment system for hospital services in Serbia and projected payments under diagnostic related groups system in urology - Babić Uroš; Soldatović Ivan; Vuković Dejana; Šantrić-Milićević Milena; Stjepanović Mihailo; Kojić Dejan; Argirović Aleksandar; Vukotić Vinka (Vojnosanitetski Pregled, 2015)
Background/Aim. Global budget per calendar year is a traditional method of funding hospitals in Serbia. Diagnose related groups (DGR) is a method of hospital payment based on classification of patients into groups with clinically similar problems and similar utilization of hospital resources. The aim of this study was to compare current methods of hospital services payment with the projected costs by DRG payment method in urology. Methods. The data were obtained from the information system used in the Clinical Hospital Center “Dr. Dragiša Mišović” - Dedinje in Belgrade, Serbia. The implemented hospital information system was the main criterion for selection of healthcare institutions. The study included 994 randomly selected patients treated surgically and conservatively in 2012. Results. Average costs under the current payment method were slightly higher than those projected by DRG, however, the variability was twice as high (54,111 ± 69,789 compared to 53,434 ± 32,509, p < 0,001) respectively. The univariate analysis showed that the highest correlation with the current payment method as well as with the projected one by DRG was observed in relation to the number of days of hospitalization (ρ = 0.842, p < 0.001, and ρ = 0.637, p < 0.001, respectively). Multivariate regression models confirmed the influence of the number of hospitalization days to costs under the current payment system (β = 0.843, p < 0.001) as well as under the projected DRG payment system (β = 0.737, p < 0.001). The same predictor was crucial for the difference in the current payment method and the projected DRG payment methods (β = 0.501, p <0.001). Conclusion. Payment under the DRG system is administratively more complex because it requires detailed and standardized coding of diagnoses and procedures, as well as the information on the average consumption of resources (costs) per DRG. Given that aggregate costs of treatment under two hospital payment methods compared in the study are not significantly different, the focus on minor surgeries both under the current hospital payment method and under the introduced DRG system would be far more cost-effective for a hospital as great variations in treatment performance (reduction of days of hospitalization and complications), and consequently invoiced amounts would be reduced.